Fabrication and Characterization of Copper Matrix Composites Reinforced Silver-Coated Carbon Fibres - Kamardin, A; Derman, MNB; Rahmat, A; Mohd Salleh, MAA (International Journal of Engineering and Technology, 2018)
Silver interface was developed to improve the thermal properties of copper matrix reinforced carbon fibre. The composites were made by coating the carbon fibres with silver and copper layers via the electroless coating process. The thermal conductivity and the thermal expansion of the composites were profiled by means of JMP Pro software. The experimental results showed that the weight-percent of silver and the volume-percent of the carbon fibre have significant effect on the thermal properties of the composites. The thermal conductivity and thermal expansion of the composites were also profoundly influenced by the anisotropic structure of the composites.Â Â